2018
DOI: 10.3389/fimmu.2018.00287
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intestinal Indigenous Microbiota on Intrafamilial Infection by Helicobacter pylori in Japan

Abstract: Helicobacter pylori is a causative pathogen of chronic gastritis, gastric ulcer disease, and gastric cancer. Humans are known to be a natural host for H. pylori and tend to acquire the pathogen before the age of 5 years. The infection may then persist lifelong if eradication therapy is not applied. One of the modes of transmission of H. pylori is between family members, and therefore, the presence of infected family members is an important risk factor in children. However, other environmental factors have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
1
15
0
1
Order By: Relevance
“…Osaki et al 30 conducted a study in Japan by analyzing whether gut microbiota may affect intrafamilial H pylori transmission. The composition of gut microbiota among members of the same family was found to be very similar; however, no difference in gut microbiota was noted between H pylori-positive and -negative subjects.…”
Section: Is There a Role For Other Gut Microbiota In H Pylori Transmentioning
confidence: 99%
“…Osaki et al 30 conducted a study in Japan by analyzing whether gut microbiota may affect intrafamilial H pylori transmission. The composition of gut microbiota among members of the same family was found to be very similar; however, no difference in gut microbiota was noted between H pylori-positive and -negative subjects.…”
Section: Is There a Role For Other Gut Microbiota In H Pylori Transmentioning
confidence: 99%
“…Family microbiota is shared between parents and children and may play an important role in the composition of infant microbiota. Whether intestinal microbiota can affect H. pylori intrafamilial infection has been investigated (Osaki et al 2018). The microbiota composition of 18 fecal specimens from five H. pylori-infected children and their family members were analysed in five families.…”
Section: 1a-2 Microbiotamentioning
confidence: 99%
“…Additionally, a Japanese study of 1,123 adult subjects, using 16S rRNA amplification from fecal samples, also confirmed higher abundance of Lactobacillus in H. pylori -infected subjects with severe atrophic gastritis (Iino et al, 2018). However, there has been only one study related to fecal microbiota and H. pylori infection in children, which included 18 fecal samples from five Japanese families (Osaki et al, 2018). These indicated a similar composition of intestinal microbiota between members of the same family, but the sample size was small.…”
Section: Introductionmentioning
confidence: 99%